Valorization of various sources of rabbit manure in agro-piscicultural system in Benin (West Africa): dynamics and effect of mineralization upon quality of fresh water - Richard Adande; Hervé Kouessivi Janvier Bokossa; Mouhamadou Nourou Dine Liady; Emile Didier Fiogbé (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Rising demand of fish generates various pressures on aquatic ecosystems, causing its deterioration and the loss of its biodiversity. With the aim of a better management and fish production in a salubrious environment, this study proposes the utilization of organic fertilizers from rabbit manure. Methods The treatments consisted of manure of rabbits fed with: manufactured diet (T1), improved diet with Ipomea aquatic (T2), improved diet with Elaeis guineensis (T3), and improved diet with Panicum maximum (T4). Indeed, experimental design was a completely randomized block design with three replications. 6 g in 10 L of water from the different manures from each diet was followed during 50 days. Various nutrients were measured. Results After the mineralization process, the best manure which released more nutrients was T4 with measured proportions of N-NO2 −, N-NO3 −, N-NH3, P-PO4 3−, Ca2+, Mg2+, K+, and suspended matter being 0.06 ± 0.0, 0.38 ± 0.1, 0.85 ± 0.1, 8.27 ± 0.9, 12.11 ± 0.8, 4.47 ± 0.3, 3.02 ± 0.2, and 140.78 ± 18.6 mg/L, respectively. The highest content of phosphorus and nitrogen was recorded in T4 and T2, respectively. The principal component analysis showed a positive correlation between P-PO4 3−, Ca2+, Mg2+, MES, conductivity, and salinity during mineralization. Conclusion Manure from rabbits fed by an improved diet with P. maximum (T4) was recommended for agro-piscicultural production system.